An examination of the structure of executive compensation and sustainability - Teng, Arthur (2011)
Many studies have been done on the relationship between executive compensation against economic, environmental and social performance, which are the underlying elements of sustainability. This paper seeks to understand whether there is a direct link between compensation and sustainability, and came up with two general hypotheses. We gathered data from IT firms listed in the S&P 500 from the period between 2006 and 2008.